Concrete around us. Building and climate change - Piróg, Marek (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2023)
Concrete is a valuable material that is widely used by the modern construction industry. It has many valuable advantages and unique properties, hence its widespread use, and not only for the construction of objects. The scale of its use has been the subject of many discussions with regard to the environmental impact and significant CO2 emissions that accompany its production and subsequent application. The article starts by presenting the scale of production of this material, its advantages and importance for the construction industry. This is followed by an attempt to determine how to optimize its use. Finally, the article raises issues related to the possibility of using alternative solutions to concrete structures and products based on a concrete mix, after which final conclusions are presented.